Borderline resectable pancreatic cancer: More than an anatomical concept. Issue 2 (February 2017) - Petrelli, Fausto; Inno, Alessandro; Barni, Sandro; Ghidini, Antonio; Labianca, Roberto; Falconi, Massimo; Reni, Michele; Cascinu, Stefano; ,
Abstract: Borderline resectable pancreatic cancer (BRPC) accounts for about 10–15% of newly diagnosed pancreatic cancer, and its management requires a skilled multidisciplinary team. The main definition of BRPC refers to resectability, but also a high risk of positive surgical margins and recurrence. This raises questions about the value of surgery and suggests an opportunity to utilize preoperative treatment in this subset of patients. Besides technical borderline resectable disease which is defined on anatomical and radiological criteria, there is also a biological borderline resectable disease which is defined on clinical and biological prognostic factors. Technical borderline resectable disease requires tumor shrinkage with aggressive therapy including modern drug combinations +/− radiotherapy to achieve radical surgery. Biological BRPC needs always an early systemic treatment in order to select the best candidates for subsequent radical surgery. It is important to distinguish between these different clinical scenarios, both in clinical practice and for clinical trials design.